A simple interfacial pH detection method for cationic amphiphilic self-assemblies utilizing a Schiff-base molecule. Issue 6 (19th February 2016) - Sarkar, Yeasmin; Das, Sanju; Ray, Ambarish; Jewrajka, Suresh K.; Hirota, Shun; Parui, Partha Pratim
Abstract : A simple pH-sensing method to monitor interfacial pH deviation from the bulk pH for cationic micelle and vesicle is introduced by estimating the change in the Schiff-base molecule (AH) proton dissociation between interface and bulk. Abstract : A simple pH-sensing method for cationic micelle and vesicle interfaces is introduced, utilizing a Schiff-base molecule, 2-((4 H -1, 2, 4-triazol-4-ylimino)methyl)-6-(hydroxymethyl)-4-methylphenol (AH). AH containing a phenolic moiety was obtained by the reaction between 4-amino-4 H -1, 2, 4-triazole containing polar O- and N-centres with opposite polarity to the cationic interface and 2-hydroxy-3-(hydroxymethyl)-5-methylbenzaldehyde. The acid/base equilibrium of AH was investigated at the interfaces of cetrimonium bromide (CTAB) micelles, tri-block-copolymeric micelles (TBPs) and large unilamellar vesicles (LUVs) of different lipid compositions using steady state UV-Vis absorption spectroscopy. AH interacted strongly with the micelle and vesicle interfaces, according to the binding studies with LUV. A larger amount of AH proton dissociation was observed when localized at the interface of micelles and vesicles compared to that in the bulk phase, indicating that the pH values at the cationic interfaces are higher than in the bulk phase. The pH values were about 2.2 and 1.6 units higher at the CTAB and TBP micelle interfaces, respectively, than the bulk pH. The pH variation decreased from 2.4 to 1.5 units by increasing the neutral 1, 2-dioleoyl- sn-glycero -3-phosphocholine (DOPC) lipid content from 0 to 50% in the cationic dimethyldioctadecylammonium (DDAB) LUV, indicating that the interfacial positive charges are responsible for the higher interfacial pH. Detailed structural and absorption characteristics of neutral AH and its anionic A − forms were investigated by fluorescence spectroscopic measurements and DFT based theoretical calculations. The present simple pH detection method may be applied to various biological micelle and vesicle interfaces.